Facile synthesis of monodispersed silver nanoparticles on graphene oxide sheets with enhanced antibacterial activity - Liu, Lei (2012)
Graphene oxide-Ag nanoparticle (GO-Ag) composites were synthesized through a facile two-phase 10 (toluene-water) process. Transmission Electron Microscope and X-ray diffraction analysis revealed that the Ag nanoparticles anchored on GO sheets were spherical in shape and highly monodispersed with uniform size of 6 nm. The antibacterial activity of GO-Ag composites was investigated against gram-negative bacteria Escherichia coli (E.coli) and showed a remarkably enhanced antibacterial activity compared with the original Ag nanoparticles, suggesting that the as-prepared nanocomposites may be 15 used as effective antibacterial materials